Answer:
3
Step-by-step explanation:
Because in 3xy 3 is the numerical coefficient
Answer:
A political strategist wants to test the claim that the percentage of residents who favor construction is more than 30%, so then that represent our claim and needs to be on the alternative hypothesis.
Based on this the correct system of hypothesis are:
Null hypothesis: ![p \leq 0.3](https://tex.z-dn.net/?f=p%20%5Cleq%200.3)
Alternative hypothesis ![p >0.3](https://tex.z-dn.net/?f=p%20%3E0.3)
Step-by-step explanation:
We have the following info given from the problem:
the random sample of voters selected from the town
represent the proportion of residents favored construction
represent the value desired to test.
A political strategist wants to test the claim that the percentage of residents who favor construction is more than 30%, so then that represent our claim and needs to be on the alternative hypothesis.
Based on this the correct system of hypothesis are:
Null hypothesis: ![p \leq 0.3](https://tex.z-dn.net/?f=p%20%5Cleq%200.3)
Alternative hypothesis ![p >0.3](https://tex.z-dn.net/?f=p%20%3E0.3)
And in order to test this hypothesis we can use a one sample z test for a population proportion and the statistic would be given by:
(1)
And with the data given we have:
Note: a radioactive decay constant is always negative.
time = [natural log(ending amount / beginning amount)] / k
time = ln (20 / 24) / -.00011
time = ln (5/6) / -.00011
time = -.018232155683 / -.00011
time =
<span>
<span>
<span>
165.7468698455
</span>
</span>
</span>
time =
<span>
<span>
<span>
165.75 years
</span></span></span>
Answer:
Possible committee structures = 293930
Step-by-step explanation:
The combination expression is used here
²¹C₉ = 21!/(9!(21−9)!) = 293930
Multiplying complex numbers is a lot like multiplying binomial terms. The only relation one has to remember when dealing with complex numbers is that i² = -1.
Now let us try to multiply binomials. This is done by adding the products of the first term of the first binomial distributed to the second binomial, and the second term of the first binomial distributed to the second binomial. This is done below:
(<span>3 – 5i)(–2 + 4i) = -6 + 12i + 10i -20i²
</span>
Simplifying and applying i²<span> = -1:</span>
-6 + 22i - 20(-1)
-6 + 22i + 20
14 + 22i
Among the choices, the correct answer is B.